Financial Vulnerability and Financial Instruments: Evidence from Mexico - Díaz, Daniela Fernanda; Di Giannatale, Sonia; Rojas, Irvin (Sobre México : temas de economía, 2023)
We perform an empirical analysis to quantify the effect of holding financial instruments, such as savings and credit, on the financial vulnerability of households. Financial vulnerability refers to their capacity to withstand adverse economic shocks and fulfill regular payment obligations. Utilizing data from the 2018 National Survey of Financial Inclusion in Mexico, we construct a financial vulnerability index and perform a propensity score matching analysis to estimate the effect of holding financial instruments on financial vulnerability. Our findings indicate that holding savings instruments, both formal and informal, as well as formal credit, mitigate financial vulnerability. However, we also find that having informal credit contributes to an increase in financial vulnerability.